1993
DOI: 10.1111/j.1600-0536.1993.tb03430.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational allergic contact dermatitis caused by exposure to acrylates during work with dental prostheses

Abstract: Between 1974 and 1992, we were consulted by 4 patients (an orthodontist, 2 dental technicians and a dental worker trained in-house) who had developed occupational allergic contact dermatitis from working with dental prostheses. All patients had positive allergic patch test reactions to methyl methacrylate (MMA), the acrylate which is the most widely used in work with prostheses. All but the orthodontist also reacted to dimethacrylates, which are used in cross-linked dental prostheses. The last patient, investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
67
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 24 publications
1
67
1
2
Order By: Relevance
“…26 Acrylic monomers can cause irritant contact dermatitis as well as allergic contact dermatitis reactions. 27 Our research found that for dental technicians the primary source of adverse reactions was acrylic resin. This is not surprising when we consider that methyl methacrylate is a potent sensitiser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Acrylic monomers can cause irritant contact dermatitis as well as allergic contact dermatitis reactions. 27 Our research found that for dental technicians the primary source of adverse reactions was acrylic resin. This is not surprising when we consider that methyl methacrylate is a potent sensitiser.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising when we consider that methyl methacrylate is a potent sensitiser. 27 It has been reported that the incidence of contact dermatitis to methacrylate resins in dental personnel is increasing due to the increased use of methacrylate containing materials (compomers, composites, RMGICs) to replace amalgam as a restorative material, especially in Europe. 20 The timescale of the ARRP is still too short to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…This is because their contact with soft tissues, such as skin, induces adverse effects and delayed-type hypersensitivity. To date, dental researchers have reported that an allergic reaction was observed in patients who came into repeated contact with 2-HEMA, thereby developing delayed-type hypersensitivity due to exposure to this compound during work [14][15][16] . Latex gloves cannot protect the skin against the contact of 2-HEMA, because the latter permeates through rubber gloves 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, uncured methacrylate monomers can be absorbed through the skin [22] and cause allergic reactions (e.g. dermatitis) [23,24]. In addition, the toxicity of methacrylate esters is theorized to involve alkylation of critical cellular nucleophiles via Michael addition [25].…”
Section: Discussionmentioning
confidence: 99%